PERCEPATAN PEMETAAN KADASTER MEMANFAATKAN TEKNOLOGI WAHANA UDARA TANPA AWAK - Catur Aries Rokhmana (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2013)
Since May 2013, the National Land Agency has begun serving Thematic Map production. This implies that thereis some additional workload on the ongoing land register mapping. Therefore, it will be necessary to develop efficienttechnology to accelerate the production of cadastal maps. Nowadays, the remote sensing technologies using high-resolutionsatellite imagery has been used to produce maps, such as Land Use map, in BPN. To some needs, as a matter of fact, there arestill weaknesses on remote sensing technology. This paper is aimed at introducing the use of unmanned aereal vehicletechnology (UAV) to accelerate the production of thematic mapping. This technology is able to produce a sharper orthophotoin seeing parcel objects rather than that of satellite imagery. It has the production capacity of > 300Ha per day. Theinexpensive and portable instrument led the idea of “on demand mapping” and the establishment of an efficient photogrammetricsurveyor team that can serve in a relatively small area (<5.000Ha). The mapping will be done in locations with small changeor the location needing a need a quick response. Moreover, there is no need to wait for a wide area as well as the use of remotesensing technology or conventional air mapping. Using the UAV for mapping technology can produce images with a value of<20cm Ground Sampling Distance (GSD) with average Horizontal positional accuracy of approximately 2 times GSD.Keywords: Cadaster mapping and land use map, orthophoto image, unmanned aerial vehicle.